2022
DOI: 10.1186/s12931-022-02240-1
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical development of a long-acting trivalent bispecific nanobody targeting IL-5 for the treatment of eosinophilic asthma

Abstract: Background Eosinophilic asthma is a common subtype of severe asthma with high morbidity and mortality. The cytokine IL-5 has been shown to be a key driver of the development and progression of disease. Although approved monoclonal antibodies (mAbs) targeting IL-5/IL-5R have shown good safety and efficacy, some patients have inadequate responses and frequent dosing results in medication nonadherence. Results We constructed a novel trivalent bispecif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Due to the non-recognition of murine albumin by our HSA Nb, the majority of Nectin-4 NDCs are cleared through renal elimination within 48 h. In our previous study, trivalent Nbs containing HSA Nb demonstrated a prolonged residence time of up to 12 days in cynomolgus monkeys [ 55 ]. Consequently, our Nectin-4 NDCs may potentially maintain a comparable half-life in cynomolgus monkeys and the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the non-recognition of murine albumin by our HSA Nb, the majority of Nectin-4 NDCs are cleared through renal elimination within 48 h. In our previous study, trivalent Nbs containing HSA Nb demonstrated a prolonged residence time of up to 12 days in cynomolgus monkeys [ 55 ]. Consequently, our Nectin-4 NDCs may potentially maintain a comparable half-life in cynomolgus monkeys and the human body.…”
Section: Discussionmentioning
confidence: 99%
“…Human CTGF domain II (AA101-167) was optimized using a human codon and synthesized into the pFUSE vector (Invitrogen, Carlsbad, CA, USA), as previously described. 21 , 24 CTGF domain II-Fc was expressed in HEK-293F cells (American Type Culture Collection) and purified by protein A affinity chromatography. The purified antigen was mixed with Freund’s adjuvant and immunized with two young camels.…”
Section: Methodsmentioning
confidence: 99%
“…Anti-CTGF Nb was screened through phage display bio-panning according to established methods. 21 , 26 , 27 To identify positive colonies, individual colonies from the library were randomly selected for periplasmic extract ELISA verification. After sequencing of the screened colonies, the CTGF-specific Nb gene was amplified and subcloned into the pFUSE-mFc vector.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These treatments include (i) Sonelokimab (M1095) targeting interleukin-17A/F for psoriasis, (ii) Gefurulimab (ALXN1720) targeting autoantibodies against acetylcholine receptors for generalized Myasthenia gravis, (iii) Nb M6495 targeting A Disintegrin and Metalloproteinase with Thrombospondin Motifs-5 for osteoarthritis, and (iv) Nb V565 against tumor necrosis factor for Crohn’s Disease [ 138 , 139 , 140 , 141 ]. To further illustrate the potential of Nbs in therapeutics against autoimmune disorders, potential Nb candidates against eosinophilic asthma and multiple sclerosis have also been identified [ 142 , 143 ].…”
Section: Therapeutical Applications Of Nanobodiesmentioning
confidence: 99%